Computed Tomography for 4-Dimensional Angiography and Perfusion Imaging of the Prostate for Embolization Planning of Benign Prostatic Hyperplasia. Issue 10 (October 2019) - Kobe, Adrian; Puippe, Gilbert; Klotz, Ernst; Alkadhi, Hatem; Pfammatter, Thomas
Abstract : Objectives: The aim of this study was to evaluate the feasibility of a computed tomography (CT) protocol enabling the visualization of the prostatic artery (PA) before prostatic artery embolization (PAE) in benign prostatic hyperplasia, which provides quantitative perfusion information of the prostate gland. Materials and Methods: In this institutional review board–approved study, 22 consecutive patients (mean age, 67 ± 7 years) who were planned to undergo PAE underwent a dynamic CT scan of the pelvis (scan range, 22.4 cm; cycle time, 1.5 seconds; scan time, 44 seconds; 25 scan cycles; 70 kVp; 100 mAs) after the administration of 70 mL of iodinated contrast media (flow rate, 6 mL/s; 10 seconds' delay). Image postprocessing consisted of a spatiotemporal, frequency-depending multiband filtering technique with noise reduction, motion correction, resulting in (1) time-resolved, temporal maximum intensity projection (MIP) images from fusion of multiple arterial time points; (2) 4-dimensional (4D) CT angiography images after bone and calcium plaque removal; and (3) parametric perfusion maps of the prostate. Intraprocedural cone-beam CT was performed with a microcatheter in the PA. In both modalities, the contrast-to-noise ratio of the right internal iliac artery or the PA was calculated, respectively. Visibility of the PA was scored using a Likert scale (score 1 = not seen, to score 4 = intraprostatic PA branches seen). Quantitative perfusion analysis of the dynamic pelvic CT included calculation of the blood flow, blood volume, mean transit time, and flow extraction product. Results: The average volume CT dose index and dose length product of CT was 35.7 ± 6.8 mGy and 737.4 ± 146.3 mGy·cm, respectively. Contrast-to-noise ratio of the pelvic vessels on temporal MIP images and cone-beam CT were 45 ± 19 and 69 ± 27, respectively ( P < 0.01). The mean visibility score of the PA was 3.6 ± 0.6 for 4D-CT angiography and 3.97 ± 0.2 for cone-beam CT ( P < 0.001). The PA was visualized in 100% of 4D-CT angiography examinations, with one PA being visible only proximally. Prostate CT perfusion analysis showed blood flow, blood volume, mean transit time, and flow extraction product values of 27.9 ± 12.5 mL/100 mL/min, 2.0 ± 0.8 mL/100 mL, 4.5 ± 0.5 second, and 12.6 ± 5.4 mL/100 mL/min, respectively, for the whole prostate gland. About half the patients showed a pronounced difference between the lobes. Conclusions: We introduced a CT protocol for PAE planning providing excellent visualization of the PA on temporal MIP images and 4D-CT angiography at a reasonable dose and low contrast volume. In addition, quantitative perfusion information is available, which might be useful for outcome prediction after embolization.